ANALISIS PENERAPAN TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP PENGGUNAAN MEDIA SOSIAL OLEH STAKEHOLDER PARIWISATA KOPI RIGIS LAMPUNG BARAT - Ningtias, Fina Agus Suci; Ali, Suprihatin; Saptiani, Fenny (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
This study aims to determine the magnitude of the influence of the application of the technology acceptance model (TAM) on the use of social media by tourism stakeholders of Kopi Rigis Lampung Barat with critical mass variables, capability to use social media perceived ease of use, perceived usefulness, behavior to use, and actual system usage conditions. This type of research is explanatory research, with a sample of 100 respondents. The data analysis technique used is quantitative analysis using the application of the technology acceptance model (TAM) and structural equation test based on variance Partial Least Square (PLS) with the SmartPLS test. The results showed that critical mass had no significant effect on perceived ease of use, critical mass had a significant effect on perceived usefulness, capability to use social media had a significant effect on perceived usefulness, capability to use social media had a significant effect on perceived ease of use, perceived ease of use had a significant effect on perceived usefulness, perceived ease of use had a significant effect on behavior to use, perceived ease of use had a significant effect on the real conditions of using the system, perceived usefulness had no significant effect on behavior to use, perceived usefulness had a significant effect on real conditions of using the system, and behavior to use had a significant effect on real conditions of using the system. Key Words: Technology Acceptance Model, Social Media, Tourist